A perspectiva teÃrica da cibercultura e formaÃÃo docente na visÃo dos licenciandos da UFC sobre o LaboratÃrio Interdisciplinar de FormaÃÃo de Educadores (LIFE): desafios e avanÃos - Jaiza Helena MoisÃs Fernandes (2014)
It aims to understand how the undergraduates of UFC courses experience MDCR (Network Collaborative Digital Materials) proposed by the Project LIFE (Teacher Training Interdisciplinary Laboratory) in the theoretical perspective of cyberculture. This training involved copyright collaborative activities (through the development of MDCR), face-to-face and online interactions as well as the mobilization of teaching knowledge in line with the principles of the LIFE Project and Cyberculture. Specifically, the study intended to describe how the undergraduates participate and appropriate of LIFE training, from their point of views; to identify, with support on the perception of the undergraduate students, the teaching knowledge mobilized in training and how this knowledge dialogues with the principles of LIFE / UFC training and cyberculture and to see how the development process of MDCR, teaching strategies and learning developed by the undergraduates are related to the principles of cyberculture. The work expresses theoretical discussions of cyberculture, education, teacher training, teaching knowledge, complexity and interdisciplinarity. It is a qualitative ethnographic research, which had activities at LIFE-UFC and in a basic vocational school, partner in the project. Four undergraduates, both male and female and from four courses of UFC, participated in the study. The research techniques adopted were: participant observation, semi-structured interviews and documentary analysis. The results showed that the undergraduates in graduation phase externalize the existence of gaps in basic training with regard to teaching practice, particularly in relation to aspects of cyberculture and interdisciplinarity. For the undergraduates, LIFE articulated theory and practice and potentiated teaching experiences via cybercultural and interdisciplinary experiences â in the development of MDCR and in the established relationship with the students of the partner school â who want to teach. It was concluded that LIFE training is configured as a practical training for the undergraduates that sought it in the project, once it approximates the design elements of cyberculture and interdisciplinary school. The study showed, based on the contributions of the undergraduates, the need for discussions in the academy and school about the current policies of teacher training.